Dodecagonal plasmonic quasicrystals for phage-based biosensing. (25th July 2018) - Rippa, M; Castagna, R; Zhou, J; Paradiso, R; Borriello, G; Bobeico, E; Petti, L
Abstract: In this work, we fabricate and characterize a novel sensitive two-dimensional surface enhanced Raman spectroscopy (SERS) substrate made of plasmonic nanocavities in a photonic quasicrystal arrangement characterized by a 12-fold rotational symmetry. Our SERS device is capable of detecting chemisorbed bacteriophages at a femtomolar range. Most importantly, the paper presents for the first time a study on the procedure to functionalize the plasmonic quasicrystal with bacteriophages of the Podoviridae family. The immobilization of the phages on the plasmonic substrate has been studied and verified through SERS measurements. A new stable peak, visible in the SERS spectra at 1326 cm −1 at a greater than 60 times amplification, confirms the immobilization of the phages on the substrate. This functionalization approach can be used also for other types of phages or plasmonic sensors and hence, our achievements could allow the development of novel systems for the specific detection of different species of bacteria.